Identification and validation of reference genes for qRT-PCR analysis in mulberry (Morus alba L.) - Dai, Fanwei (PLoS One, 2018)
Mulberry (Morus alba L.) is an important economic tree species in many countries. Quantitative real time PCR (qRT-PCR) has become a widely used method for gene expression studies in plants. A suitable reference gene is essential to ensure accurate and reliable results for qRT-PCR analyses. However, no reports describing the selection of reference genes have been published for mulberry. In this work, we evaluated the stability of twenty candidate reference genes in different plant tissues and under different stress conditions by qRT-PCR in mulberry using algorithms in two programs—geNorm and NormFinder. The results revealed that TUB2, UBI4, ACTIN3 and RPL4 were ranked as the most stable reference genes in the samples subsets, whereas EF1α4 and TUB3showed the least stability with both algorithms. To further validate the stability of the reference genes, the expression patterns of six genes of mulberry were analyzed by normalization with the selected reference genes. Our study will benefit future analyses of gene expression in mulberry.